Pengaruh Kualitas Produk dan Harga Terhadap Kepuasan Pengepul Pisang di Kabupaten Oku Selatan (Studi Kasus Desa Rantau Panjang Kecamatan Buay Rawan Kabupaten Ogan Komering Ulu Selatan) - Setiono, Asep; Alam, Iskandar Ali (Jurnal EMT KITA, 2023)
This study aims to determine the effect of banana collectors' satisfaction on product quality and price of bananas. Data collection was carried out by distributing questionnaires via Google from banana collectors in the district. South Oku as many as 68 copies. The data analysis method used is multiple linear regression analysis, with validity, reliability, classical assumption tests and hypothesis testing. then processed using Statistical Product and Service Solutions version 20. The results showed that product quality had a positive and significant effect on the satisfaction of collectors in the district. South OKU. In addition, price also has a positive and significant effect on the satisfaction of collectors in the South OKU district.